2017
DOI: 10.1177/1745691617692105
|View full text |Cite
|
Sign up to set email alerts
|

Narcissistic Force Meets Systemic Resistance: The Energy Clash Model

Abstract: This article focuses on the interplay between narcissistic leaders and organizations. It attempts to capture the gist of this interplay with a model outlining the narcissistic organizational trajectory. The Energy Clash Model borrows and adapts a phase/state physics metaphor to conceptualize narcissism as a force that enters or emerges in a stable system (i.e., organization) as a leader, destabilizes it, and stabilizes it at a different state or is expelled.The model consists of three time-contingent phases: p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
95
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 107 publications
(113 citation statements)
references
References 238 publications
(297 reference statements)
3
95
0
3
Order By: Relevance
“…Narcissists can exert substantial influence in social groups (see Sedikides & Campbell, 2017). The extent to which individual group members identify with and are loyal to groups, moreover, can have significant consequences for groups (Dess & Shaw, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Narcissists can exert substantial influence in social groups (see Sedikides & Campbell, 2017). The extent to which individual group members identify with and are loyal to groups, moreover, can have significant consequences for groups (Dess & Shaw, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…They view themselves as special, unique, and great—what Ernest Jones () labeled “the God Complex”—while fantasizing about power, status, and social recognition (Zeigler‐Hill et al, ). Finally, they are argumentative and antagonistic (Sedikides & Campbell, ).…”
Section: Narcissismmentioning
confidence: 99%
“…Moreover, when they receive negative feedback, they blame others (Campbell, Reeder, Sedikides, & Elliot, ) or disengage from its consequences (Thomaes & Sedikides, ). Overall, then, narcissists are no more effective or competent than non‐narcissists in the agentic domain (Sedikides & Campbell, ), although this conclusion needs to be qualified; narcissists perform relatively well when they believe that winning a competition will reap them the benefits of acclaim (Wallace & Baumeister, ).…”
Section: Narcissismmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the prominence of CEO's photographs in companies' annual reports is positively associated with CEO's narcissism levels (Chatterjee & Hambrick, 2007;Sedikides & Campbell, 2017). Also, some studies have reported a positive relation between first-pronoun use and narcissism (Chatterjee & Hambrick, 2007;Fast & Funder, 2010;Raskin & Shaw, 1988; but see Carey et al, 2015).…”
Section: Consumer Choices Self-referencing and State Narcissismmentioning
confidence: 99%